Stem cell – based gene therapy - Nazir, Z.; Irshad, S. (Вiopolymers and Cell, 2013)
Stem cells have huge potential for regenerative medicine. Adult stem cell (HSC)-based therapies have been proved to be safe and efficient for several decades, and adult MSC therapies are showing efficacy in some experiments while in other trials mixed results are obtained such as only short lived effects due to poor cellular retention or other reasons that have to be further tested. Although iPSCs might suggest a great hope for the stem cell therapy, still there are important safety issues to be considered before these cells are marketed for clinical trials. However, the advanced potential to generate stem cell lines, matched to a particular patient, and to perform homologous gene correction or targeted transgene insertion into a safe dock site in the genome prior to further expansion and differentiation offer great prospects for future regenerative medicine. Furthermore, the development of the recombinant adeno-associated virus (rAAV) technology and the use of the Zinc Finger Nuclease (ZFN) technology are promoting the homologous recombination as a best possible tool for stem cell-based gene therapy. Стовбурові клітини мають величезний потенціал для регенеративної медицини. Протягом десятиліть було доведено безпеку і ефективність терапії на основі HSC, у той час як використання MSC, обмежене строками зберігання клітин та деякими іншими причинами, лише в окремих експериментах давало позитивні наслідки з короткочасною дією, які потребують подальшого вивчення. Незважаючи на те, що ІПСК залишаються основним джерелом при терапії стовбуровими клітинами, як і раніше, існують серйозні питання біобезпеки, які потрібно враховувати особливо в разі клітин, що продаються для клінічних випробувань. Тим не менш, найперспективнішими для регенеративної медицини майбутнього є лінії стовбурових клітин, створені для конкретного пацієнта, а також коригування гомологічних генів і вбудовування трансгена в певне місце в геномі для подальшої експресії і диференціювання. Крім того, розвиток рекомбінантної аденовірусної технології (rAAV) і використання нуклеази цинкового пальця (ZFN) дозволяє вважати гомологічну рекомбінацію найкращим інструментом для генної терапії, заснованої на стовбурових клітинах. Стволовые клетки обладают огромным потенциалом для регенеративной медицины. На протяжении десятилетий были доказаны безопасность и эффективность терапии на основе HSC, в то время как использование MSC, ограниченное сроками хранения клеток и некоторыми другими причинами, лишь в отдельных экспериментах давало положительные результаты с кратковременным действием, что требует дальнейшего изучения. Несмотря на то, что на ИПСК возлагают большие надежды при терапии стволовыми клетками, по-прежнему существуют серьезные вопросы биобезопасности, которые нужно учитывать особенно в случае клеток, продающихся для клинических испытаний. Тем не менее, наибольшим потенциалом для регенеративной медицины будущего обладают линии стволовых клеток, созданные для конкретного пациента, а также корреляция гомологичных генов и встраивание трансгена в определенное место в геноме для дальнейшей экспрессии и дифференциации. Кроме того, развитие рекомбинантной аденовирусной технологии (rAAV) и использования нуклеазы цинкового пальца (ZFN) позволяет считать гомологичную рекомбинацию наилучшим инструментом для генной терапии, основанной на стволовых клетках.